Cellular senescence-related gene signatures in idiopathic pulmonary fibrosis: insights from bioinformatics - Weng, Shuting; Zuo, Jingye; Mo, Jiali; Ye, Leping (Frontiers in Immunology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive lung disease characterized by irreversible lung tissue scarring. Cellular senescence (CS) plays a significant role in IPF pathogenesis, yet the specific molecular mechanisms remain unclear. This study aimed to identify key CS-related differentially expressed genes (CS-DEGs) and investigate their potential as diagnostic biomarkers and therapeutic targets for IPF.MethodsBioinformatics analysis was conducted on the GSE53845 dataset to identify CS-DEGs in IPF. Gene set enrichment analysis (GSEA), protein-protein interaction (PPI) network analysis, and functional enrichment analyses were performed to explore the biological functions and pathways associated with CS-DEGs. External validation of the identified CS-DEGs was performed using two independent datasets, GSE32537 and GSE24206. Immunofluorescence staining on lung tissue samples from IPF patients and normal controls was performed to validate the expression of key CS-DEGs.ResultsA total of 122 DEGs were identified, and 8 core CS-DEGs were selected. CDKN2A, VEGFA, SOX2, and FOXO3 were validated as key CS-DEGs, with high diagnostic potential for IPF. Functional enrichment analysis revealed their involvement in critical biological pathways, including cellular senescence, immune response, and fibrosis regulation. Immunofluorescence staining confirmed higher expression of CDKN2A and SOX2, and lower expression of FOXO3 and VEGFA in IPF lung tissues compared to normal controls.ConclusionThis study highlights the significant role of CS-related genes in the pathogenesis of IPF and identifies four key CS-DEGs (CDKN2A, SOX2, FOXO3, and VEGFA) that could serve as potential biomarkers and therapeutic targets for IPF, providing a basis for further research.